The equivalent expression is
. Option B
<h3>How to determine the expression</h3>
Given the expression
= ![\frac{18x\sqrt{14x^8} }{6\sqrt{7x^4} }](https://tex.z-dn.net/?f=%5Cfrac%7B18x%5Csqrt%7B14x%5E8%7D%20%7D%7B6%5Csqrt%7B7x%5E4%7D%20%7D)
Divide the multipliers, we have
= ![\frac{3x\sqrt{14x^8} }{7x^4}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%5Csqrt%7B14x%5E8%7D%20%7D%7B7x%5E4%7D)
Let factorize the numerator in square root
= ![\frac{3x \sqrt{7x^4 * 2x^4} }{7x^4}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%20%5Csqrt%7B7x%5E4%20%2A%202x%5E4%7D%20%7D%7B7x%5E4%7D)
Eliminate the like factor in both the numerator and denominator
= ![3\sqrt{2x^4}](https://tex.z-dn.net/?f=3%5Csqrt%7B2x%5E4%7D)
Let's bring forth the 'x' factor, we have
= ![3x^4\sqrt{2}](https://tex.z-dn.net/?f=3x%5E4%5Csqrt%7B2%7D)
Thus, the equivalent expression
. Option B
Learn more about algebraic expression here:
brainly.com/question/723406
#SPJ1